Determinants of Tabarru’ Fund Proportion In Family Takaful in Indonesia - Siti Ulviatul Arofah; Novi Puspitasari; Lilik Farida (Institute for Research and Community Empowerment (LPPM TAZKIA), 2019)
This paper aims to analyze the determinants of the proportion of tabarru’fund in family takaful in Indonesia at the periods 2012 – 2016. Insurance growth reach 75% which 60% came from family takaful. Family takaful implements separation on fund management. Fund management with fund separation is in line with Shariah Split Fund Theory which in practice requires proportion. The method used in the research data is panel data regression. The independent variables of this study are claims (Cit), retakaful (RTit), commission fees (CFit), and administrative and general expenses (AGit). The dependent variable of this study is the proportion of tabarru’fund (Tit). The sample was chosen by using purposive sampling method and obtained sample member as many as 15 companies of Takaful. The results of this study indicate that claims affect the proportion of tabarru’ fund and these variables as determinant of tabarru’ fund proportion. While retakaful have not positive effect on the proportion of tabarru’ fund, and then commission fees and administrative and general expenses have not negative effect on the proportion of tabarru’ fund.